The profile of the Montessori assistant: historical paths and new education projects - De Serio, Barbara (Studi sulla Formazione/Open Journal of Education, 2016)
This paper looks at the professional profile of the Montessori-trained teacher, as educated at the college devised by Maria Montessori and founded in the 1950s by one of her closest pupils, Adele Costa Gnocchi. The Montessori assistant was a professional figure specially trained to aid the birth process and the “mental” needs of the protagonists involved, referring specifically to the child. In this respect, the paper also looks at the subject of education from birth, starting with Montessori’s earliest ideas on new-born children and their creative capabilities. The purpose is to recover the scientific foundations on which the pedagogical practices usually applied by childhood services are based, with the awareness that these consolidated practices need strengthening and a scientific foundation – including on an historical level – in order to contribute to qualifying services for early childhood. Through specific methodological qualification, above all with regard to Montessori’s methods, as well as by placing more valid historical importance on the paths they began, early childhood services may even be able to move in the direction of possible institutionalised training.